Ligand Coupling and Decoupling Modulates Stem Cell Fate (Adv. Funct. Mater. 8/2023). (16th February 2023) - Thangam, Ramar; Kim, Seong Yeol; Kang, Nayeon; Hong, Hyunsik; Lee, Hyun‐Jeong; Lee, Sungkyu; Jeong, Daun; Tag, Kyong‐Ryol; Kim, Kanghyeon; Zhu, Yangzhi; Sun, Wujin; Kim, Han‐Jun; et al.
Abstract : Ligand Coupling In article number 2206673, Heemin Kang and co‐workers demonstrate controllable coupling of movable nano‐ligands to immovable nano‐ligands by pulling linker molecules. The movable nano‐ligands can be decoupled from the immovable nano‐ligands by releasing linker molecules. This control of ligand coupling and decoupling dynamically regulates the focal adhesion, mechanosensing, and differentiation of stem cells.